Induction of Labor in Post-Term Nulliparous and Parous Women – Potential Advantages of Misoprostol over Dinoprostone - Tsikouras, P.; Koukouli, Z.; Manav, B.; Soilemetzidis, M.; Liberis, A.; Csorba, R.; Trypsianis, G.; Galazios, G. (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: We undertook a prospective cohort study to compare the effectiveness and safety of 50 µg misoprostol versus 3 mg dinoprostone in two vaginal doses 6 hours apart, followed if necessary by oxytocin for labor induction in low-risk post-term (> 40 weeks) pregnancies with unfavorable cervix (Bishop score ≤ 6). Methods: Labor induction and subsequent management were conducted using a standardized protocol. The primary outcome of the study was labor induction rate. Secondary outcomes included mode of delivery, time interval from induction to delivery, maternal complications and neonatal outcome. Results: 107 patients received misoprostol (Group A) and 99 patients received dinoprostone (Group B). Compared with group A, more women in Group B needed a second vaginal dose of prostaglandin or oxytocin infusion in order to proceed to labor (21.5 vs. 43.4 %; p = 0.01). Misoprostol alone as a single or double vaginal dose was more effective than dinoprostone alone in inducing labor without oxytocin administration (85.0 vs. 50.4 %; p = 0.04). Overall, the rate of successful induction of labor did not differ between groups (91.6 vs. 85.8 %; p = 0.75). Vaginal delivery, operative vaginal delivery and Caesarean section rates were not significantly different. Time interval from induction to delivery however, was shorter for Group A (median 11 hours vs. 14.1 hours; p < 0.001). Though emergency Caesarean section due to fetal distress was more frequent in Group A (16.8 vs. 4.0 %; p = 0.007), low Apgar scores < 7 and NICU admissions did not differ significantly. Maternal complications, mostly not serious, were higher in Group A (31.8 vs. 2.0, p < 0.001). Conclusion: Misoprostol is a more effective agent than dinoprost in post-term pregnancy for labor induction with few maternal adverse effects.
Keywords: misoprostol; dinoprostone; labor induction; post-term pregnancy